Perbedaan Waktu Paparan Mengubah Pola Interaksi Molekular Antigen-Receptor-Antibodi – Sebuah Contoh Penggunaan Model Kompleks Glikoprotein Virus (Hhv-6b), Host Receptor Dan Monoklonal Antibodi - Bernadette Dian Novita Dewi (JURNAL WIDYA MEDIKA, 2018)
A binding interaction between a foreign glycoprotein molecule (antigen) and a receptor molecule on one or more antibodies (immunoglobulins) are the major soluble molecules produced to know the pattern of specific and avid of inhibition the antibody to virus replication, aseffective defensive role for the antibody response.This antibody also has molecular competitive pattern of antibody – receptor to antigen complexbind.However, incubation time differences could alter the patterns of those interaction. An antibody that has got neutralizing effect and high index of binding affinity could be considered asanti virus candidate.